1984
DOI: 10.2527/jas1984.582386x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and Conjugative Metabolism of Xenobiotics by Livers of Cattle, Sheep, Swine and Rats1

Abstract: Homogenate preparations from fresh livers of cattle, sheep, swine and rats were assayed for microsomal cytochrome P-450 content, for mixed-function oxidase activities and for a wide array of conjugative activities using numerous xenobiotic substrates. Results show that hepatic enzymatic capabilities toward xenobiotics do not parallel phylogenetic classifications, thus strengthening the view that most of the comparative data available at present is more descriptive than predictive of relationships among species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
2

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 35 publications
1
21
1
2
Order By: Relevance
“…1998). This may be, in part, a function of differences in the activity of liver enzymes involved in the degradation of EDCs; for example, there are differences between ruminants, pigs and rodents in this factor (Smith et al. 1984; Watkins and Klaassen 1986).…”
Section: An Insidious and Significant Threat – A Considered View?mentioning
confidence: 99%
“…1998). This may be, in part, a function of differences in the activity of liver enzymes involved in the degradation of EDCs; for example, there are differences between ruminants, pigs and rodents in this factor (Smith et al. 1984; Watkins and Klaassen 1986).…”
Section: An Insidious and Significant Threat – A Considered View?mentioning
confidence: 99%
“…Αυτό αντανακλά στις διαφορές των ειδών στο μετα βολισμό του ήπατος και ιδιαίτερα στις επιπτώσεις εξω γενών ή ενδογενών στεροειδών ουσιών στην ηπατική λειτουργία (Colby, 1980). Στα μηρυκαστικά, οι επι δράσεις των μικροβιακών πληθυσμών της μεγάλης κοι λίας στην αποικοδόμηση των EDCs και στην απορρό φηση τους μπορεί να είναι περισσότερο σημαντικές από τους βιομετασχηματισμοΰς στο ήπαρ (Smith et al, 1984).…”
Section: ε) απορρόφηση μεταβολισμός και συσσώρευσηunclassified
“…Early comparative metabolic studies on the rate of biotransformation of model substrates in liver microsomes show that there may be important differences in metabolic rates of alkoxyresorufins between sheep and cattle. Smith et al (1984) found that hepatic EROD in cattle (n=5) was 14 fold higher than in sheep (n=5). This difference was confirmed in a study carried out in cultured hepatocytes isolated from sheep (n=3) and cattle (n=4) showing a 3-fold greater EROD activity in cattle cells (Van t' Klooster et al, 1993).…”
Section: Comparative Expression and Activity Of Cyp1 Enzymes In Sheepmentioning
confidence: 99%